Fenomena No Viral No Justice di Indonesia (Analisis Wacana) - Ulfah, Harniati (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
There is an interesting phenomenon from a number of media used by the public in recent times. This phenomenon is virality in social media. The purpose of this research is to find out the virality of a case and find out the consequences of virality on the handling of the case.  The research method used in this paper is non-interactive qualitative research, often referred to as analytical research. The process undertaken is data collection, case identification, analysis, and synthesis of data to then provide interpretations of several viral events in various media.This paper finds that the viral case occurred through various social media applications that developed in the community such as TikTok, Facebook, X, as well as online news media. The result of this viral case was a re-investigation by the police. In terms of media transformation theory, it can be said that the virality of a news story can have an impact on the authorities or related institutions to reinvestigate a fairly old case. This is evidenced by the reinvestigation of the viral case by the police until it was retried even to the Supreme Court. This response from the authorities also proves that the delivery of aspirations through virality is effective and influential for the community and related institutions.Keywords: no viral no justice, virality, social media, related institutions